Sustainability, reliability, and durability of civil engineering structures - Tomaszewska, Agnieszka; Szafran, Jacek; Brune, Bettina; Wilde, Krzysztof (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
.